Uric acid and sphingomyelin enhance autophagy in iPS cell-originated cardiomyocytes through lncRNA MEG3/miR-7-5p/EGFR axis - Yinyin Cao; Junxiang Wen; Yang Li; Weicheng Chen; Yao Wu; Jian Li; Guoying Huang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
This study aimed to determine the metabolites associated with ventricular septal defect (VSD) and the underlying mechanisms. Blood samples and thymus tissues were collected from VSD patients to perform LC-MS-based metabolomics assay and generate iPS cell-derived cardiomyocytes, respectively. VSD rat model was used in vivo study. RT-PCR, western blotting, immunohistochemistry, luciferase activity assay, GFP-LC3 adenovirus and GFP and RFP tfLC3 assay, and transmission electron microscopy were performed to investigate the underlying mechanisms. The metabolites uric acid (UA) and sphingomyelin (SM) increased in the serum of VSD patients, along with enhanced autophagy. The combination of UA and SM treatment could promote autophagy and inhibit EGFR and AKT3 expressions. Overexpression of EGFR and AKT3 suppressed autophagy in UA and SM-treated cardiomyocytes, respectively. Also, lncRNA MEG3 knockdown and overexpression could enhance and inhibit autophagy in UA and SM-treated cardiomyocytes, respectively, through targeting miR-7-5p. Moreover, miR-7-5p mimics and inhibitors promoted and inhibited autophagy in UA and SM-treated cardiomyocytes, respectively, via target EGFR. In VSD rat model, upregulation of MEG3 could reverse high level of autophagy and decrease serum UA and SM. In conclusion, UA and SM are essential VSD-associated metabolic biomarkers and MEG3/miR-7-5p/EGFR axis is critical to the regulation of autophagy in cardiomyocytes.